Interest in Saving Students at Sharia Banks in Jayapura City, Papua Province - Irmalasari Duwi Lestari; Hajrah Putri Febriani; Jukri Baharuddin; Fachrudin Fiqry Affandy (AL-ARBAH: Journal of Islamic Finance and Banking, 2023)
AbstractPurpose - This study aims to determine the effect of attitude variables, subjective norms and perceived behavioral control on the interest of IAIN Fattahul Muluk Papuan students in saving at Islamic banks.Method - This research is a quantitative study using multiple regression analysis method with three X variables and one Y variable where the data in this study were obtained from 70 students who were collected by distributing questionnaires.Result - The results of this study indicate that subjective attitudes and norms have no effect on students' interest in saving in Islamic banks. Only behavioral control has a significant effect on students' interest in saving in Islamic banks.Implication - This research has implications for controlling student behavior about Islamic banking by holding courses on Islamic banking that make students aware of banking products and services. Furthermore, to improve attitudes and subjective norms among students, so that the interest in saving at Islamic banks is further enhanced.Originality - This study saw firsthand that subjective attitudes and norms had no effect on students. Only behavioral control affects students so that later it can influence other students to save at Islamic banks.